Relationship Analysis Of Reading Skills Level On Student Learning Outcomes In SD IT Darul Adzkia - Rahma Zahidah; Eka Yusnaldi (At-Tarbiyat, 2022)
The problem experienced by teachers is the low level of students' reading skills. This study aims to (1) find out the relationship between the level of reading skills on learning outcomes, (2) find out the obstacles experienced by students in improving reading skills, (3) find out the factors that cause barriers to improving reading skills, (4) find efforts to overcome barriers in improving reading skills. This type of research is descriptive qualitative. Collecting data in this research is using the methods (1) Observation, (2) Test, (3) Documents, and (3) Interview. The data that has been collected will be reprocessed through the stages of data reduction, data display, and concluding. The subjects of this study were students from each class at SD IT Darul Adzkia, Tebing Tinggi City. While the object of this research is the level of students' ability in reading and student learning outcomes. The results of the study found factors that affect the level of children's reading skills. This study also found a relationship between the level of reading skills with children's learning outcomes. This research has had a positive impact on improving children's reading skills and children's learning outcomes.